The impact of collaboration between science and religious education teachers on their understanding and views of argumentation - Chan, J; Erduran, S (Springer Nature, 2022)

(untitled)
Teachers’ understanding and teaching of argumentation is gaining more attention in science education research. However, little is known about how science teachers engage in argumentation with teachers of different subject taking an interdisciplinary perspective that may inspire new pedagogical ideas or strategies. In particular, the positioning of argumentation at the juncture of science and religion is rare. This paper reports an empirical study involving science and religious education (RE) teachers who collaborated on teaching argumentation in three secondary schools in England. Their interdisciplinary collaboration was sustained by a series of professional development sessions over 18 months. Analysis of the interview data unfolds how the teachers’ collaboration impacted their understanding of argumentation and views of teaching their subject. Through working relationally in exploring and teaching argumentation, the science teachers reflected more notable changes than their RE counterparts. Science teachers came to appreciate student voice in the learning process and the role of argumentation in fostering students’ scientific reasoning. The paper is a salient step to researching argumentation in a cross-curricular terrain, particularly in relation to RE. It also sheds light on how collaborating with teachers of another subject bolstered science teachers’ professional development and broke subject barriers.